Inspirasi ide-ide kreatif : untuk modifikasi busana muslim/muslimah otodidak, murah, dan praktis / A. Nur Ayatillah al-Azizy; editor, Munnal Hani'ah - NUR AYATILLAH AL-AZIZY, A. (Harmoni, 2010)
222 hlm. : ilus. ; 23 cm.